Chemical and physical modifications of starch for renewable polymeric materials. (March 2020) - Ojogbo, E.; Ogunsona, E.O.; Mekonnen, T.H.
Abstract: Biodegradable polymers obtained from renewable natural resources have received increasing attention due to their potential as alternatives to traditional petroleum-based plastics. Among the various sources, polysaccharides stand out as a highly convenient feedstock because they are readily available, renewable, inexpensive, and provide great stereochemical diversity. Starch, a renewable polysaccharide polymer, has been well researched and attracted commercial interest as a feedstock due to its renewability, biodegradability, low cost, and abundance of –OH chemistry, leaving it open to endless modification possibilities and melt processability in the presence of plasticizers. However, its hydrophilicity, thermal, and mechanical properties limitations, rapid degradability, and strong intra and intermolecular hydrogen bonding of the polymer chains hinder its melt processability and limit its widespread commercial application as a renewable biopolymer. Therefore, modification is necessary to mitigate these limitations and bring about other desirable properties. This article critically reviews the recent progress achieved in the modification of starch for industrial biopolymer material applications where starch is used as one of the major constituents.